Importance of Collaboration Supported Context in Blended Learning - Ulmane-Ozoliņa, Lāsma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Higher education institutions in their study process often uses blended-learning. Blended learning is pedagogically meaningful integration of e-learning and traditional education approach. To involve students in more active participation in study process there is need for collaboration supported context. Context with choices for students to collaborate in assignment completition. Quaziexperiment at Liepaja Univeristy showed that students appreciate possibility to collaborate on assignments using technology, at this case Moodle, and they choose to collaborate even its not set as compulsory condition.